2009
DOI: 10.1001/archdermatol.2009.262
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mapping in 2 Large Multigenerational Families With CYLD Mutations

Abstract: Objective To comprehensively ascertain the extent and severity of clinical features in multiple affected individuals from two large families with proven heterozygous mutations in the CYLD locus and to correlate these findings with the three appendageal tumor predisposition syndromes, familial cylindromatosis (FC), Brooke-Spiegler syndrome (BSS), and multiple familial trichoepitheliomas (MFT) known to be associated with such germline mutations. Design Inter- and intra-familial observational study. Setting T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 44 publications
5
59
0
5
Order By: Relevance
“…We observed that keratin K5 and K10 expression was also downregulated in most of the tumor islets of the three types of familial cylindromatosis tumors (Figure 5m-r). These results show that, as occurs in CYLD C/S tumor cells, where the lack of the deubiquitination function of CYLD was accompanied by diminished expression of Maspin, in tumor cells of cylindromatosis patients carrying a functionally similar inactivating mutation in the CYLD gene (Rajan et al, 2009), a decreased expression of Maspin was also observed.…”
Section: Maspin Expression Is Decreased In Human Cylindromas Trichoesupporting
confidence: 64%
“…We observed that keratin K5 and K10 expression was also downregulated in most of the tumor islets of the three types of familial cylindromatosis tumors (Figure 5m-r). These results show that, as occurs in CYLD C/S tumor cells, where the lack of the deubiquitination function of CYLD was accompanied by diminished expression of Maspin, in tumor cells of cylindromatosis patients carrying a functionally similar inactivating mutation in the CYLD gene (Rajan et al, 2009), a decreased expression of Maspin was also observed.…”
Section: Maspin Expression Is Decreased In Human Cylindromas Trichoesupporting
confidence: 64%
“…Mutations in introns leading to intronic exonization and large deletions have been reported in some of those ‘negative' cases [30,34]. So far, no genotype-phenotype correlation has been found [11,17,35]. Bigger cohorts with accurate correlation of molecular, clinical and histomorphologic data may eventually help in developing prognostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the diagnosis of BSS, mutation analysis of the CYLD gene was performed by sequence analysis of all coding exons [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], exon/intron boundaries and Q-PCR analysis (laboratory of the Department of Clinical Genetics of Erasmus MC, Rotterdam, The Netherlands). A splice-site mutation, 2350+5G>A in the exon 17 of the CYLD gene was found.…”
Section: Case Reportmentioning
confidence: 99%
“…The most common tumour types include trichoepitheliomas, cylindromas and spiradenomas originating from the basal cell layer of the epidermis and fi-om hair follicles in the areas of the head and neck (3,4). In some patients BSS may cause turban tumour (5).…”
mentioning
confidence: 99%